قصيدة " بشرى للجزائر" لمحمد العيد آل خليفة مقاربة أسلوبية - مسعي, أحمد عمار (جامعة الوادي - university of Eloued, 2020)
يمثل هذا المقال قراءة على ضوء المنهج الأسلوبي في قصيدة "بشرى للجزائر" للشاعر الجزائري محمد العيد آل خليفة، الذي يعد من أبرز شعراء الجزائر والذي واكب أحلك الظروف التي مرت بها، ولقد أخترت المنهج الأسلوبي منهجا لدراسة القصيدة، لأنه ينطلق من البنية والنسق اللغوي ويحلل الخطاب الشعري مركزا على جوانبه المتعددة، فبدأـت الدراسة بالمبحث الدلالي ومنتجاته البلاغية، من تشبيه واستعارة، وكنايه ومجاز، ثم بالمبحث التركيبي الذي بدأته بالمفردات التي هي أساس التركيب، ثم الجمل وأنماطها المختلفة، والتي تقودنا إلى المبحث الموسيقي بوصفه الإطار الشكلي الحامل للموضوع الشعري، وتقدم الدراسة تعريفا للأسلوبية وأهم مصطلحاتها، وأهم اتجاهاتها. الكلمات المفتاحية : مقاربة ؛ أسلوبية ؛ قراءة ؛ قصيدة؛ الشعر؛ محمد العيد. Abstract: This article is a reading in the light of the stylistic approach in the poem "Bouchra Algeria" by the Algerian poet Mohammed Al-Eid Al-Khalifa, who is considered one of the most prominent poets of Algeria and who accompanied the darkest circumstances that have passed, and I chose the stylistic approach to study the poem, because it stems from the structure and language format and analyzes The poetic discourse focuses on its multiple facets. The study began with semantic research and its rhetorical products, from metaphor and metaphor, and then to the structural study that began with the vocabulary which is the basis of the structure and then the sentences and their different patterns. Ml of the poetic theme. The study presents a definition of stylistics and its most important terms.
مقال
Keywords: مقاربة ; أسلوبية ; قراءة ; قصيدة ; الشعر ; محمد العيد